Whose Victims and Whose Survivors? Polish Jewish Refugees between Holocaust and Gulag Memory Cultures - Zessin-Jurek, Lidia (Holocaust and genocide studies, 2022)
Holocaust and Gulag studies are witnessing the belated emergence of the Soviet experience of Jewish escapees from Nazi-occupied Poland as a lieu de mémoire in its own right. Although not commemorated in official ritual, museum spaces, or memorial sites, the sheer mass of published testimonies by survivors of this experience far outweighs the previous lack of attention to the refugees’ story. It was the agency of the refugee survivors themselves which subsequently put their Soviet experience on the mnemonic map of World War II. This article discusses both the reasons for that lack of attention and the current growing interest in their accounts. It proposes a typology based on questions of victimhood and perpetratorship, analyzed through the contrast between the way the Jewish exiles in the USSR interpreted their experiences and how those who experienced the Holocaust directly interpreted theirs. The article thus asks, whose victims did the refugees consider themselves, the Germans’ or the Soviets’?